Optimizing the strategy for developing wood craft production at MSME Laser Production - Marlina Kurnia; Dani Ashari; Bagas Setiawan Nugroho; Octa Via Rista; Ahmad Setyo Nugroho; Tintrin Tintrin (Universitas Muhammadiyah Magelang, 2022)
Children's car craft is one of the most popular business activities in Magelang City. UMKM activities in Magelang City still have many weaknesses in production, human resource management, marketing, development, and bookkeeping. The purpose of this program is to help Laser Production SMEs in Bojong Hamlet Rt 01 Rw 09, Kel. South Jurangombo, South Magelang in achieving production targets and maximum profits. The methods used are socialization, training and assistance related to optimizing production, bookkeeping and digital marketing. The results of this program are increasing partner skills related to increasing the number of production, financial management, digital marketing, and human resources (HR). This training activity increases the knowledge and skills of partners in optimizing the amount of production that has the potential to increase partners' income.